REBUNG BAMBU SEBAGAI ALTERNATIF FITOHORMON DALAM MEMACU PERTUMBUHAN TUNAS, PADA BENIH DORMAN - annisa adelia nur rahmawati (JURNAL VIGOR, 2021)
This study aims  to determine the use of bamboo shoots as an alternative phytohormones in spurring shoot growth in dormant seeds. Bamboo shoots contain calcium (Ca), magnesium (Mg), phosphorus (P), potassium (K), sodium (Na), various vitamins and other minerals. Based on several studies, it was shown that the use of bamboo shoots by means of extraction can spur growth in candlenut seeds, sengon seeds, and cayenne seeds.